Mitigation of vertical motion in planing crafts for enhanced operationability in seaways using passive energy absorbers – A test of concept. (15th November 2022) - Allaka, Himabindu; Farid, Maor; Groper, Morel
Abstract: High-speed planing crafts operating in seaways encounter high impact loads. The resulting extreme motions and accelerations adversely affect the craft's structural integrity and payload, and pose a risk to the onboard crew, thus limiting their year-round operability. Reducing the vertical acceleration and motions of these crafts in a seaway may ensure structural integrity, increase navigation safety, and extend their operational envelope. This study examines the effectiveness of deploying a linear passive energy absorber (PEA) – a tuned mass damper (TMD) – to mitigate the planing craft's vertical motion. Nonlinear equations of motion for the TMD installed on the planing craft operating in an irregular seaway were developed, and its effectiveness was evaluated and verified using numerical simulations. A significant reduction in the unwanted heave motions was observed around the sea states (SS) and the craft speeds used to fine-tune the TMD parameters. The effectiveness of the TMD, however, severely diminished in other SS and at other craft speeds. Based on our results, the application of the TMD to mitigate vertical motions of planing crafts seems an impractical solution. Other passive energy absorbers, such as nonlinear-PEAs or nonlinear energy sinks, should be considered as a way to address the TMD's shortcomings. Highlights: Dynamic modeling of high-speed planing crafts with motion mitigation in the longitudinal plane. The effectiveness of passive energy absorbers for mitigation of heave motion on planing crafts. Analyzing the effectiveness of linear passive energy absorbers for motion mitigation in regular and irregular seas.